The effect of thermal to the diameter of Nd : YAG crystal during growth process - Ahmad Kamaruddin, Wan Khairul; Rohani, Md. Sopar; Md. Rahim, Sahar (Faculty of Science University Teknologi Malaysia, 2008)

(untitled)
The Nd:YAG crystal grown in a pure argon atmosphere using Czochralski method with ADC (Automatic Diameter Control) r.f. heating is reported.The conditions required to grow Nd:YAG single crystals are described. The pull rate was 0.75 mm/h with a seed rotation of 15 rpm. All runs were made with growth along the c-axis <111> direction.